Natural hazards, disasters and violence against women and girls: a global mixed-methods systematic review - Meghna Ranganathan; Heidi Stöckl; Alyssa Mari Thurston (BMJ Global Health)
Introduction Disasters triggered by climate and other natural hazards are increasing in frequency, severity and duration worldwide. Disasters disproportionately impact women and girls, with some evidence suggesting that violence against women and girls (VAWG) increases in disaster settings. Suggested risk factors for postdisaster VAWG include increased life stressors, failure of law enforcement, exposure to high-risk environments, exacerbation of existing gender inequalities and unequal social norms. We aim to systematically appraise the global literature on the association between disasters from natural hazards and VAWG.Methods We conducted a systematic review using the following databases: Embase, Global Health, Medline, PubMed and Social Policy and Practice and searched grey literature. We included quantitative, qualitative or mixed-methods studies published in English language that examined the association between disasters from natural hazards and VAWG. We summarised the findings using a narrative synthesis approach.Results Of 555 non-duplicate records, we included a total of 37 quantitative, qualitative and mixed-methods studies. Among the quantitative studies, eight studies found a positive association between disaster exposure and increased VAWG, and four additional studies found positive associations with some violence types but not others. Qualitative findings offered insights into three hypothesised pathways: disaster exposure associated with (1) an increase of stressors that trigger VAWG; (2) an increase of enabling environments for VAWG and (3) an exacerbation of underlying drivers of VAWG.Conclusion As the first known global systematic review on the relationship between disasters from natural hazards and VAWG, this review contributes to the evidence base. We were limited by the quality of quantitative studies, specifically study designs, the measurement of variables and geographic scope. The severe health consequences of VAWG and increasing frequency of extreme events means that rigorously designed and better quality studies are needed to inform evidence-based policies and safeguard women and girls during and after disasters.